Profitability of Industrial Product Service Systems (IPS²) – Estimating Price Floor and Price Ceiling of Innovative Problem Solutions - Steven, M.; Rese, M.; Soth, T.; Strotmann, W.-C.; Karger, M. (Cranfield University Press, 2009)
Companies from industrialised nations are faced with the threat of competition from low-cost countries. We suggest Industrial Product Service Systems (IPS²) as a possible answer. But as the development and production can be quite expensive for the supplier, the question arises how the net benefits of an IPS² for the supplier can be determined to ensure that the IPS² is profitable. We establish a framework for the calculation of both the supplier’s revenues and costs of an IPS². Requirements induced by possible subsequent changes of the IPS² are emphasized. We propose a combination of the Net Present Value Approach and the Real Options Approach as a means of determining the quantified revenues and a combination of Direct Costing, Time-Driven Activity-Based Costing and the Real Options Approach for the calculation of the costs of an IPS² for a supplier over its life cycle.
Organised by: Cranfield University
Keywords: Industrial Product Service Systems; Net Present Value Approach; Real Options Approach; Time Driven; Activity-Based Costing; Learning Effects; Price Ceiling